HLA class II antigens in Croatian patients with pemphigus vulgaris and their correlation with anti-desmoglein antibodies - Lakoš Jukić, Ines; Mokos, Mislav; Marinović, Branka (Frontiers in Immunology, 2023)
Pemphigus vulgaris (PV) is an acquired autoimmune blistering disease characterized by the production of autoantibodies targeting desmosomal cadherins, primarily desmoglein 1 and desmoglein 3, leading to acantholysis. The etiology of PV is multifactorial, including genetic susceptibility. This retrospective study aimed to evaluate the association of HLA class II alleles and PV and to examine the impact of PV-associated HLA class II alleles on the concentration of anti-desmoglein antibodies. The study group included 30 patients in whom the diagnosis of PV was confirmed by histopathological analysis, immunofluorescence findings, and ELISA testing for detecting antibodies against desmoglein 1 and desmoglein 3. HLA class II alleles were typed by polymerase chain reaction with sequence-specific primers (PCR-SSP). The control group consisted of 190 healthy volunteer blood donors. Data analysis revealed a significantly higher frequency of HLA class II alleles in our population of patients with PV, including HLA-DRB1*04:02, HLA-DRB1*14:54, HLA-DQB1*03:02, HLA-DQB1*05:03, HLA- DQA1*03:01, and HLA-DQA1*01:04, as well as a significantly lower frequency of HLA-DQA1*05:01 compared to the control group. We have also investigated the influence of risk alleles for PV, recognized in almost all study populations, HLA-DRB1*04:02 and HLA-DQB1*05:03, on the concentration of antibodies against desmogleins 1 and 3 in relation to the presence of these alleles. The results showed significantly higher levels of antibodies directed against desmoglein 3 among patients with DRB1*04:02 compared to patients without this allele. No difference was found for anti-desmoglein 1 antibodies. Regarding DQB1*05:03 allele, statistical analysis showed no differences in the concentration of anti-desmoglein antibodies in patients carrying this allele versus those without it.